(NkONSTRUIROWANIE WEROQTNYH KRISTALLI^ESKIH STRUKTUR MINERALOW (B/s - (NuRUSOW(B, (NwADIM sERGEEWI^s; (NdUBROWINSKAQ(B, (NnATALXQ aNATOLXEWNAs; (NdUBROWINSKIJ(B, (NlEONID sEMENOWI^s ((NmOSKWA (B:s (Nmgu(B,s, 1990)
(NbIBLIOGR(B.: (NS(B. 118-127 (135 (NNAZW(B.)s
Keywords: (NkRISTALLI^ESKAQ STRUKTURAs; (NmINERALYs